2014
DOI: 10.1111/jere.12046
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Structure and the Choice of Price versus Quantity in a Mixed Duopoly

Abstract: We consider the choice of price/quantity by a public and a private firm in a mixed differentiated duopoly. First, we study the way in which the strategic choice of the market variable is affected by different given organizational structures (managerial or entrepreneurial) of the public and the private firm. Second, we investigate how the price/quantity choice interacts with the endogenous choice of the organizational structure, thus determining a subgame perfect equilibrium at which firms choose to behave as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 31 publications
1
19
1
Order By: Relevance
“…Further, in this paper, we show that in the endogenous selection of the strategic contracts of the public firm and the private firm, there exists no equilibrium market structure in the new delegation system where the public firm adopts the delegation contract on the basis of social welfare and the difference between consumer surplus and producer surplus whereas the private firm adopts the sales delegation contract, since the combination of the strategic contracts of the public and private firms does not coincide with each other, given the strategic contract of their respective rival firm. However, provided the strategic contractor the rival for both firms, it is noteworthy that their optimal strategic contracts are different from the new delegation system in this paper and the sales delegation case in Chirco et al (2014).…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…Further, in this paper, we show that in the endogenous selection of the strategic contracts of the public firm and the private firm, there exists no equilibrium market structure in the new delegation system where the public firm adopts the delegation contract on the basis of social welfare and the difference between consumer surplus and producer surplus whereas the private firm adopts the sales delegation contract, since the combination of the strategic contracts of the public and private firms does not coincide with each other, given the strategic contract of their respective rival firm. However, provided the strategic contractor the rival for both firms, it is noteworthy that their optimal strategic contracts are different from the new delegation system in this paper and the sales delegation case in Chirco et al (2014).…”
Section: Introductionmentioning
confidence: 84%
“…Thus, we realize that as the delegation parameter of the public firm becomes higher, the owner of the public firm gives more emphasis to consumer surplus than to producer surplus in all the four games. 9 As described below in detail, in the case wherein the owners of both the public and private firms provide to their managers the sales delegation contracts, Chirco et al (2014) showed that there does not exist any equilibrium market structure under the class of pure strategies on the strategic contracts of the public and private firms. Further, in this paper, we show that in the endogenous selection of the strategic contracts of the public firm and the private firm, there exists no equilibrium market structure in the new delegation system where the public firm adopts the delegation contract on the basis of social welfare and the difference between consumer surplus and producer surplus whereas the private firm adopts the sales delegation contract, since the combination of the strategic contracts of the public and private firms does not coincide with each other, given the strategic contract of their respective rival firm.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Haraguchi and Matsumura (2014) showed that this result holds, regardless of the nationality of the private firm Chirco et al (2014). showed that both firms choose a price contract when the organizational structure is endogenized.…”
mentioning
confidence: 87%